Visualizing pseudo‐ductility in carbon/glass fiber hybrid composites manufactured using infusible thermoplastic Elium® resin - Khan, Tayyab; Ali, Muhammad A.; Irfan, Muhammad S.; Cantwell, Wesley J.; Rehan, Umer (Polymer composites, 2023)
In this study, two different type of glass and carbon fiber hybrid laminates were manufactured using a low‐viscosity thermoplastic resin that is, Elium®. A detailed microstructure visualization study was conducted using X‐ray computed tomography (XCT) analysis. The viscoelastic properties were examined through dynamic mechanical analysis. The mechanical performance was investigated through flexural and tensile tests along with a fractographic study using optical and scanning electron microscopy. The XCT analysis revealed a weak interface between the Elium® resin and the glass fabric, with glass fiber specimens exhibiting a void content of 1.24%, in contrast to the carbon fiber specimens which showed void content of only 0.28%. Therefore, adding glass fabric layers in the hybrid laminates increased the void content, which had a negative impact on the overall mechanical performance. The average flexural strength of the hybrid specimen having G2C4G2 stacking sequence was observed to be 254% higher than pure GFRPC specimens. Similarly, the tensile strength and Young's modulus of the same hybrid specimen showed 155% and 380% increases, respectively, compared to the GFRPC specimens. This increase was primarily due to higher stiffness of the carbon fibers and their better fiber – matrix interface. Whereas the tensile strain of the hybrid specimen having G3C2G3 stacking sequence was 37% higher than that of the CFRPC specimens. The SEM images highlighted fiber fracture and brittle failure modes in the carbon fiber specimens, in contrast to fiber pullout, interfacial failure, poor fiber‐matrix bonding and ductile failure modes in the glass fiber specimens.